(untitled) (Research, Society and Development, 2024)
This research describes the development and implementation of a wind tunnel experiment using recycled materials at the InterCiências Space of the Federal University of Itajubá. The overall aim of this work is to present the development of a new experiment focused on fluid mechanics, specifically a wind tunnel constructed with recycled materials, and to propose a didactic sequence for its application in a school in the South of Minas Gerais, aiming to enrich the InterCiências Space collection and fill a gap in the offering of experiments on this theme, thus contributing to a more comprehensive and contextualized scientific education for the students served. The research adopted a qualitative approach, including the construction of the experiment and the development of a didactic sequence (DS) for its application in a school in the South of Minas Gerais. The results indicated a high level of interest and enthusiasm from the students during the execution of the activities, although challenges arose in organizing ideas and applying the concepts studied. Teacher guidance was essential to mitigate these challenges and promote active student participation. The activity culminated in the creation of mental maps by the students, highlighting key concepts of fluid dynamics and the behavior of wind in relation to aircraft wings. Suggestions for future work include deepening the integration between theory and scientific practice, investigating the long-term impact of practical activities on students’ interest in science, and exploring different teacher mediation strategies during experimental activities. This study contributes to understanding the effectiveness of practical activities in promoting student engagement and consolidating scientific concepts.